The immunosuppressant Protosappanin A diminished recipient T cell migration into allograft via inhibition of IP-10 in rat heart transplant. - Maomao Zhang; Jieqiong He; Jingbo Hou; Jian Wu; Meng Sun; Jinjin Cui; Jiangtian Tian; Miaomiao Jiang; Bo Yu (PLoS ONE)
The immunosuppressant Protosappanin A (PrA), isolated from the medicinal herb, promotes cardiac allograft survival, diminishes inflammatory cell infiltration, and inhibits interferon γ-induced protein 10 kDa (IP-10) mRNA expression in rats cardiac grafts. Binding of the chemokine IP-10 to its cognate receptor, CXCR3, plays crucial roles in allograft immunity, especially by mediating the recruitment of effector T cells to allografted tissues. In this study, we attempted to determine whether PrA-mediated inhibition of IP-10 contributes to the effect of reduced T cell infiltration into cardiac allograft within a rat model. Administration of PrA (25 mg/kg daily) via oral gavage following heart transplantation significantly reduced the increase of IP-10 mRNA level in allograft and prevented IP-10 secretion by peripheral blood mononuclear cells (PBMC) isolated from recipient rats seven days posttransplantation. Furthermore, in vitro experiments demonstrated that PrA addition to control PBMC prevented IP-10 secretion. Chemotactic migration assays were utilized to evaluate recipient T cell migration towards PBMC supernatant. PrA administration impaired PBMC supernatant-induced T cell migration. Additional in vitro experiments revealed that PrA slightly reduced naïve T cell migration towards chemokines. The presence of IP-10 in PBMC supernatant prevented PrA from reducing T cell migration in PrA-treated recipients. Neither CXCR3 chemokine ligand Mig nor non-CXCR3 chemokine ligand SDF-1 had any effect on T cell migration in PrA-treated recipients. The addition of anti-CXCR3 antibody restored PrA-mediated inhibition of T cell migration. Immunofluorescence microscopy showed that IP-10 was expressed mainly in CD68 positive infiltrating monocytes. Furthermore, PrA consistently reduced CXCR3+T cell infiltration into cardiac allografts. The reduced intensity of CXCR3 staining in PrA-treated allografts contributed to the previously depressed naïve T cell migrating activity induced by PrA. Collectively, these data indicate that PrA inhibition of IP-10 activity reduced recipient T cell migration and infiltration of cardiac allografts, thus partially explaining the immunosuppressive effect of PrA.